2018
DOI: 10.3389/fnins.2018.00336
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Movement in Neurological Diseases: Effects on Neural Stem Cells Characteristics

Abstract: Both astronauts and patients affected by chronic movement-limiting pathologies face impairment in muscle and/or brain performance. Increased patient survival expectations and the expected longer stays in space by astronauts may result in prolonged motor deprivation and consequent pathological effects. Severe movement limitation can influence not only the motor and metabolic systems but also the nervous system, altering neurogenesis and the interaction between motoneurons and muscle cells. Little information is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 85 publications
(111 reference statements)
1
31
0
Order By: Relevance
“…For example, obese children have shown lower motor competence and white matter reduction in the cerebellar peduncles than their normal-weight peers (Augustijn et al, 2017). Experimental studies using mice exposed to prolonged movement restrictions has also shown negative effects on neurogenesis and the role of trophic determinants (i.e., nerve growth factor mRNA and brain-derived neurotrophic factor) involved in this phenomenon (Desaphy et al, 2005; Adami et al, 2018). Consequently, overweight/obese children may benefit more from increased cardiorespiratory fitness.…”
Section: Discussionmentioning
confidence: 99%
“…For example, obese children have shown lower motor competence and white matter reduction in the cerebellar peduncles than their normal-weight peers (Augustijn et al, 2017). Experimental studies using mice exposed to prolonged movement restrictions has also shown negative effects on neurogenesis and the role of trophic determinants (i.e., nerve growth factor mRNA and brain-derived neurotrophic factor) involved in this phenomenon (Desaphy et al, 2005; Adami et al, 2018). Consequently, overweight/obese children may benefit more from increased cardiorespiratory fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) is particularly abundant in neural stem cells (NSCs) [65,66]; indeed, the growth of NSCs is driven by the addition of epidermal growth factor (EGF) in the medium [67,68]. Based on this, we can speculate that a reduction of the proliferative capacity of NSCs, which have been found in an animal model of movement constraints, in which also the level of CDK5RAP1 was drastically reduced [69], could be related to an increase of the i 6 A intracellular form, which can induce a cytotoxic effect and increase autophagy, hence reducing cell proliferation, as demonstrated in a CIG model [59]. Indeed, the CDK5RAP1 level was found to be reduced in NSCs obtained from mice that underwent movement restraint [69], most likely because of the alteration of the proliferative and differentiative capabilities of these cells (Fig.…”
Section: Cdk5rap1mentioning
confidence: 94%
“…; Adami et al . ). From then on, new possibilities of therapeutic approaches were imagined using these cells, hypothesizing their use in different neurological pathologies such as spinal cord injury, spinal muscular atrophy, amyotrophic lateral sclerosis, and Parkinson's disease (Bottai et al .…”
Section: Neural Stem Cells Descriptionmentioning
confidence: 97%
“…Then, lower vertebrates were found to possess regenerative capacity in the central nervous system (CNS) particularly birds during the song learning phase (Alvarez-Buylla et al 1990). Only at the end of the last century were NSCs found to be present in mammals (Reynolds and Weiss 1992;Bottai et al 2003Bottai et al , 2008Givogri et al 2008;Adami et al 2018). From then on, new possibilities of therapeutic approaches were imagined using these cells, hypothesizing their use in different neurological pathologies such as spinal cord injury, spinal muscular atrophy, amyotrophic lateral sclerosis, and Parkinson's disease (Bottai et al 2003Pluchino et al 2003;Corti et al 2007;Daniela et al 2007;Givogri et al 2008;Adami et al 2014).…”
mentioning
confidence: 99%